Análisis de la cadena de valor de los productos forestales que se comercializan en el cantón de Hojancha, Guanacaste, Costa Rica. - Rodríguez-Araya, José Joaquín (Instituto Tecnológico de Costa Rica, 2011)
In Costa Rica one of the Counties pioneers in forestry is Hojancha, the eleventh County of the Province of Guanacaste. In the early decade of the Seventy's there was a financial crisis that affect it and collapsed the economy in Hojancha which base on the production of basic grains and cattle raising. Since then and through the years, the Forestry sector has contributed in the developing of the County and that is the reason why we conducted a study of the value of forest products. We gather information through surveys and interviews done to the Producers, which kindly and in good faith agree to provide us. With all the information gather and documented it data base, we proceeded to perform an analysis to determine if the Forest Producers have established controls over their cost and production, also to find out the social impact of the economy in the County. The study revealed that 87% of the forest producers in Hojancha do not perform detailed assessments of the cost used to produce their products. Only 16.8% of the Producers invest in advertising to publicize their products and services. Also was confirm the economic importance of the Forestry sector that the County receives. In the year 2011 we have estimated an income of about six hundred eighty-two million three hundred ninety-nine thousand twenty Colones, divided between seed commercialization, seedlings, lumber and crafts, and to generate 39 permanent jobs and 133 temporary jobs annually. A proposal was made to help improve all the administrative and technical process to each producer.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2011.
Keywords: Costos de producción; Publicidad; Comercialización; Empleo; Mercadeo; Semillas